Whose sexuality is it anyway? Women's experiences of viewing lesbians on screen. Issue 6 (2nd November 2017) - Scanlon, Julie; Lewis, Ruth
Abstract: While critical analyses of media representations of lesbians continue to grow, less attention is paid to audience responses to those representations. This paper explores women's experiences of viewing lesbians on screen, analysing qualitative data from focus groups with audiences of a women-only film season screened in a UK cinema: "Lesbians on Screen: How Far Have We Come?" We consider how the internalisation of the "male gaze" complicates some women's viewing of lesbian characters and how women attempt to challenge and resist that gaze through their viewing practices and strategies. We discuss audience creativity in re-signifying representations of women, as well as other strategies including choosing to view privately or in women-only spaces. These acts of resistance disrupt the dominance of the male gaze, patriarchal cinema spaces, and reception of images on screen. By examining women's reflections on the experience of being in a women-only audience, a unique cinema space that "felt free" of conventional constraints of heteronormativity and patriarchy, this paper also examines how the gendered cinema space affects audience experiences.